Analisis Peran Orang Tua Dalam Mendukung Prestasi Cabang Olahraga Bola Basket di Sekolah MA Jakarta Pusat - Wijaya, Habibi Hadi; Muhammad Rzky, Muhammad Rizky; Nurhadi, Maha Dewi Afifah; Bima Sentana, Bima Sentana; Alkautsar, Fata Azima (Jurnal Keolahragaan, 2024)
This study aims to analyze the role of parents in supporting basketball in achievement in Central Jakarta MA schools. The research method used is data collection with a distributed questionnaire questionnaire. This type of research approach uses quantitative. The entire population studied was sampled with a total of 16 basketball athletes, where the total population was female-dominated 11 (68.8%) samples, while the male population was only 5 (31.3%) samples. Data collection was carried out using a goggle form questionnaire consisting of 29 detailed statement items with the answers using a Likert scale, namely; STS, TS, S and SS, then the data was processed using SPSS 23 statistics. The number of statements is 29 item items, of which 17 are positive and 12 are negative. Of the total score there is an amount of 1,440, the average value obtained is 3,103, for the minimum value is 1 and the maximum value is 4, then the overall variant value generated is 0.086, the standard deviation value obtained as a whole is 0.186. . The results of the data show that the education of athletes includes the most 12th grade high school with a total of 10 (62.5%), while the least is in 11th grade high school with a total of 2 (12.5%). In addition, there are 100% age characteristics of athletes, they started basketball from the age of 15 to 19 years. In conclusion, the role of parents in achieving an athlete's achievement is very important and varied. First, the emotional and motivational support provided by parents can be a major driver of athlete achievement.Penelitian ini bertujuan untuk menganalisis peran orang tua dalam mendukung cabang olahraga bola basket dalam prestasi di sekolah MA Jakarta Pusat. Metode penelitian yang digunakan adalah pengumpulan data dengan angket kuesioner yang disebarluaskan. Jenis pendekatan penelitian ini menggunakan kuantitatif. Seluruh populasi yang diteliti dijadikan sampel dengan jumlah 16 atlet bola basket, dimana total populasi berdominan perempuan 11 (68,8%) sampel, sedangkan populasi laki-laki hanya 5 (31,3%) sampel. Pengumpulan data dilakukan menggunakan angket kuesioner goggle form yang terdiri dari 29 item pernyataan terperinci dengan jawaban tersebut menggunakan skala likert yaitu ; STS, TS, S dan SS, kemudian data tersebut diolah menggunakan statistic SPSS 23. Jumlah pernyataan 29 item butir soal, diantaranya terdapat 17 dinyatakan positif dan 12 dinyatakan negatif. Dari keseluruhan skor terdapat jumlah sebesar 1.440, nilai rata-rata didapatkan berjumlah 3.103, untuk nilai minimum berjumlah 1 dan nilai maksimum berjumlah 4, kemudian nilai varian keseluruhan yang dihasilkan berjumlah 0.086, nilai simpangan baku yang diperoleh keseluruhan sebesar 0.186. Hasil dari data tersebut terdapat Pendidikan atlet diantarannya paling banyak SMA kelas 12 dengan total 10 (62,5%), sedangkan paling sedikit berada di SMA kelas 11 dengan total 2 (12,5%). Selain itu terdapat karakteristik usia atlet 100% mereka memulai bola basket sejak usia 15 sampai 19 tahun. Kesimpulannya eran orang tua dalam mencapai prestasi seorang atlet sangat penting dan beragam. Pertama, dukungan emosional dan motivasional yang diberikan oleh orang tua dapat menjadi pendorong utama bagi prestasi atlet.